About the Problem of Improving the Process of Sociocultural Competence Formation of Foreign Students-Non-Philologists. - Кушнир, И. Н. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The article deals with the necessity of improving the process of sociocultural competence formation of foreign students-non-philologists at the main and advanced stages of teaching the Russian language at Ukrainian institutions. The issue under analysis is based on the differences between Russian and Ukrainian socio-cultural space. The list of communicative topics and appropriate speech intentions, selected with regard for the above-mentioned specifics of teaching Russian as a foreign language, are proposed